Sphingolipids role in the regulation of inflammatory response: From leukocyte biology to bacterial infection. Issue 3 (9th January 2018) - Chiricozzi, Elena; Loberto, Nicoletta; Schiumarini, Domitilla; Samarani, Maura; Mancini, Giulia; Tamanini, Anna; Lippi, Giuseppe; Dechecchi, Maria Cristina; Bassi, Rosaria; Giussani, Paola; Aureli, Massimo
Abstract: Sphingolipids (SLs) are amphiphilic molecules mainly associated with the external leaflet of eukaryotic plasma membrane, and are structural membrane components with key signaling properties. Since the beginning of the last century, a large number of papers described the involvement of these molecules in several aspects of cell physiology and pathology. Several lines of evidence support the critical role of SLs in inflammatory diseases, by acting as anti‐ or pro‐inflammatory mediators. They are involved in control of leukocyte activation and migration, and are recognized as essential players in host response to pathogenic infection. We propose here a critical overview of current knowledge on involvement of different classes of SLs in inflammation, focusing on the role of simple and complex SLs in pathogen‐mediated inflammatory response.